PENINGKATAN LITERASI ETIKA BISNIS DI KALANGAN MAHASISWA UNIVERSITAS BUMIGORA - Taufik, Muhammad; Jati, L. Jatmiko (CV Sentra Nusa Connection, 2024)
This activity, which was carried out on December 18rd 2023, was organized by Bumigora University Lecturers. Students or participants involved in this activity come from all classes in the Bumigora University Management Study Program. The implementation stage of this activity consists of three stages, namely planning, implementation and reflection. From the overall results of the activity, there was an increase in the participants' business ethics literacy. This is proven by the results of the pre-test and post-test. Participants have a deep understanding of the concept of business ethics and encourage the application of moral values in a business context. The team realized that this short activity still needed to be carried out and developed. So, it is hoped that all participants can implement this knowledge in real life and continue to deepen their understanding of business ethics at other opportunities.